Differences in stem water potential during oil synthesis determine fruit characteristics and production but not vegetative growth or return bloom in an olive hedgerow orchard (cv. Arbequina) - Hueso, Antonio; Trentacoste, Eduardo Rafael; Junquera, Pedro; Gómez-Miguel, Vicente D.; Gómez Del Campo, María (Elsevier, 2019)
Although oil synthesis in fruits of cv. Arbequina starts at the end of pit hardening (beginning of July in central Spain) most oil is synthesized from late summer (end August) until harvest (end October). An experiment was established in two nearby high-density olive orchards (C and L) trained in 4-m spaced hedgerows (2.3 m tall) and maintained over three successive seasons (2011–2013) to determine the effect of irrigation treatments during oil synthesis on stem water potential (Ψstem), fruit characteristics, production, water productivity (production per irrigation amount + effective rainfall), flowering and fruit-set and next-year growth. The control treatments (C1 and L1) were irrigated to maintain the “wetted” bulb near field capacity throughout the season. Three deficit-irrigation treatments were established in each orchard. In orchard C, treatments C2, C3 and C4 received 64, 38, 14% of the water applied to C1, while in orchard L, treatments L2, L3 and L4 received 71, 41, 18% of water applied to L1. The treatments produced significant differences in Ψstem that were lower in Orchard C (mean C4 value −4.91 MPa) than L (L4 −2.58 MPa) due to differences in soil depth and drip emitter spacing. At the two orchards, individually, the stressed trees were not significantly affected in terms of shoot length, flowering, fruit set, fruit abscission and consequently fruit number. While deficit irrigation significantly reduced size, oil and water content of fruit, and hence olive and oil production in Orchard C, there was no response in Orchard L. Analysis revealed that individual fruit parameters were maintained constant as Ψstem decreased during oil synthesis in response to treatment until a threshold value was reached. Oil content (% fresh weight-FW) was the least sensitive parameter (threshold −4.11 MPa) with a positive linear relationship between water and oil fruit content (R2 = 0.81). Olive production was more sensitive to Ψstem (threshold −1.82 MPa) than oil production (−2.21 MPa). Indicating that moderate stress can be applied during oil synthesis by irrigating such that Ψstem declines to the threshold value −2.21 MPa without reduction of oil production. This value corresponds to a water-stress integral of 130 MPa day−1. Maximum water productivity was achieved by irrigating at Ψstem −2.31 MPa with lower values obtained at higher or lower Ψstem. Our results indicate that Ψstem should be maintained higher than −2.21 MPa during oil synthesis for maximum production, but higher values of the water productivity will be achieved at −2.31 MPa.